Bioinformatics Analysis of a Functional ANGPT1 Variant That Interferes with miR-607 and Its Association with Susceptibility and Outcome of Ischemic Stroke in a Han Population - Chen AN; Zhong LL; Ju K; Cao H (Dove Medical Press, 2021)
Ai-Nian Chen, Ling-Ling Zhong, Ke-ju Ju, Hua Cao Department of Neurology, The Affiliated Huaian No. 1 People's Hospital of Nanjing Medical University, Huaian, Jiangsu, People's Republic of ChinaCorrespondence: Ai-Nian ChenDepartment of Neurology, The Affiliated Huaian No. 1 People's Hospital of Nanjing Medical University, 1 Huanghe Road West, Huaian, Jiangsu, 223300, People's Republic of ChinaTel +86 18751292677Email hacan979@163.comPurpose: Ischemic stroke (IS) is a major cause of disability and death. We used bioinformatics approaches to investigate a functional ANGPT1 variant that interferes with miR-607 and explored its association with IS.Materials and Methods: An IS expression microarray (GSE16561) was downloaded from the GEO and used to identify differentially expressed genes (DEGs) and functional enrichment pathways. Analyses showed that ANGPT1 participated in six key pathways and was susceptible to a key functional polymorphism rs2507799. We genotyped 567 IS patients and 500 controls for ANGPT1 rs2507799. Luciferase assays were also conducted to investigate the binding between miR-607 and ANGPT1 rs2507799.Results: In total, we identified 458 DEGs between IS patients and healthy controls in the GSE16561 dataset. GO functional enrichment analysis showed that these DEGs were mainly enriched in cell-substrate junctions, the regulation of peptide secretion, and the regulation of cytokine secretion involved in immune response. ANGPT1 rs2507799 T-carriers had a significantly higher risk of IS (Dominant model: OR = 1.48, 95% CI = 1.01- 2.17, P = 0.044). IS patients harboring the TC/TT genotype experienced significantly more severe injuries in terms of neurological function (Dominant model: OR = 2.06, 95% CI = 1.28- 3.31, P = 0.003). Analysis also showed that IS patients harboring the TC/TT genotype had a significantly worse outcome (Dominant model: OR = 2.22, 95% CI = 1.35- 3.67, P = 0.002). Luciferase assays indicated that miR-607 could affect luciferase activity by binding to the ANGPT1 mutant type.Conclusion: In this study, we used bioinformatical methods to investigate a key IS-related gene ANGPT1 and its functional polymorphism rs2507799. rs2507799 was found to be associated with a significantly increased risk for IS, a significantly more severe initial stroke severity, and a worse outcome. These results may help to improve the future management of ischemic stroke.Keywords: ischemic stroke, functional enrichment analysis, polymorphism, ANGPT1, miRNAs